( 5+ root 8) + ( 3- root 2) – ( root 2 – 6) = ________

Question

( 5+ root 8) + ( 3- root 2) – ( root 2 – 6) = ________

in progress 0
Arya 1 month 2021-08-23T00:40:34+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-23T00:41:50+00:00
    1. ( 5+root 8) + (3 – root 2 ) -(root 2 -6 )
    2. open the bracket
    3. 5+ root 8 + 3- root 2 -root 2 +6
    4. 16 +root 8 -2 root 2
    5. 16 +2 root 2 -2 root 2
    6. 2 root 2 with -2 root 2 cut
    7. therefore 16 is the answer

    0
    2021-08-23T00:41:59+00:00

    Answer:

    (5+✓8)+(3-✓2)-(✓2-6)

    =(5+✓8)+(3-✓2-✓2+6)

    =(5+✓8)+(3-2✓2+6)

    =5+✓8+3-2✓2+6

    =14+2✓2-2✓2

    =14

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )